Tuning deformation behavior of Cu0.5CoNiCrAl high-entropy alloy via cooling rate gradient: An atomistic study. (September 2019) - Feng, Shidong; Li, Lin; Chan, K.C.; Zhao, Lei; Pan, Shaopeng; Wang, Limin; Liu, Riping
Abstract: The deformation behaviors of body-centered cubic Cu0.5 CoNiCrAl high-entropy alloys processed by the cooling rate gradient are investigated by the molecular dynamics simulations. The plastic deformation ability of the high-entropy alloy is significantly improved by triggering multiple-type dislocation slips along different deformation paths. The cooling rate gradient introduces abundant atomic vacancies, proliferating the nucleation sites of dislocations. Additionally, the nucleation barriers of dislocations are reduced by the resultant structural disorder, high potential energy and chemical segregation. Consequently, the cooling rate gradient enhances the structural heterogeneity, promoting the formation of multiple deformation paths and preventing strain localization. Graphical abstract: Image 1 Highlights: The high-entropy alloys processed by the cooling rate gradient were investigated. The cooling rate gradient enhances the structural heterogeneity. The cooling rate gradient proliferates the nucleation sites of dislocations. The cooling rate gradient can trigger multiple-type dislocation slips.